Comparison of students'performance on vector concepts between Prince of Songkla University ( PSU ) and state Islamic University ( UIN ) Sunan Kalijaga Students using test of understanding of vectors ( TUV ) - Betavia Kusindrastuti (Fak. Sains dan Teknologi UIN Sunan Kalijaga, 2019)
wt,1/ ririn c.1